Identification of the trail-following pheromone receptor in termites - Diallo, Souleymane; Kašparová, Kateřina; Šulc, Josef; Johny, Jibin; Křivánek, Jan; Nebesářová, Jana; Sillam-Dussès, David; Kyjaková, Pavlína; Vondrášek, Jiří; Machara, Aleš; Lukšan, Ondřej; Grosse-Wilde, Ewald; et al. (eLife, 2025)
Pheromone communication is the cornerstone of eusocial insect societies since it mediates the social hierarchy, division of labor, and concerted activities of colony members. The current knowledge on molecular mechanisms of social insect pheromone detection by odorant receptors (ORs) is limited to bees and ants, while no OR was yet functionally characterized in termites, the oldest eusocial insect clade. Here, we present the first OR deorphanization in termites. We selected four OR sequences from the annotated antennal transcriptome of the termite Prorhinotermes simplex (Psammotermitidae), expressed them in Empty Neuron Drosophila, and functionally characterized them using single sensillum recording (SSR). For one of the selected ORs, PsimOR14, we obtained strong responses to the main component of P. simplex trail-following pheromone, the monocyclic diterpene neocembrene. PsimOR14 showed a narrow tuning to neocembrene with only one additional compound out of 67 tested generating non-negligible responses. We report on homology-based modeling and molecular dynamics simulations of ligand binding by PsimOR14. Subsequently, we used SSR in P. simplex workers and identified the olfactory sensillum responding to neocembrene, thus likely expressing PsimOR14. Finally, we demonstrate that PsimOR14 is significantly more expressed in worker antennae compared to soldiers, which correlates with higher sensitivity of workers to neocembrene.
Keywords: tykadla členovců; hmyzí proteiny; Prorhinotermes simplex; Receptors, Pheromone; receptory pachové; D. melanogaster; Isoptera; Arthropod Antennae; pheromone receptor; odorant receptor; trail-following pheromone; receptory pro feromony; Insect Proteins; termite; Pheromones; zvířata; neuroscience; deorphanization; Animals; Sensilla; feromony; sensilla; Receptors, Odorant